THE RELATIONSHIP BETWEEN SHARIA FINANCIAL INSTITUTIONS IN INDONESIA DURING THE PERIOD 2014-2018 - Maulidah Atha Mukhlifah; Sylva Alif Rusmita (Universitas Airlangga, 2020)
This study is to determine the relationship between Islamic financial institutions, both bank and non-bank financial institutions in Indonesia in the 2014-2018 period. This study uses the VAR method to process data. The results of this study are contributions from Islamic-based financial institutions in Indonesia. The Islamic capital market has a positive relationship with Islamic life insurance. This happens because, in developing countries like Indonesia, life insurance is more influential than Islamic general insurance. The relationship that occurs in the Islamic capital market and life insurance occurs because of the role of the insurance company that will buy shares in the Islamic capital market. Then, related to a negative relationship between Islamic banking and Islamic insurance. It is because every credit given by the bank will be charged for insurance. The greater the value of the credit, the higher the contribution paid. This will be considered by those who will take credit at the bank. Meanwhile, insurance companies themselves are not bound by two other financial institutions. This happens because insurance companies get capital from third parties or their customers.Keywords: Islamic Financial Institutions, Islamic Capital Markets, Islamic Banking, Islamic Insurance, VARREFFERENCE Adrian, Sutedi. (2011). Pasar modal syariah. Jakarta: Sinar Grafika.Agus D. Hardjito, Martono. (2002). Manajemen keuangan. Edisi Pertama. Yogyakarta: Ekonisia.Antonio, Karnaen Perwataatmadja dan M. Syafi’i. (1992). Apa dan bagaimana bank Islam. Yogyakarta: Dana Bhakti Wakaf.Dendawijaya, Lukman. (2009). Manajemen perbankan. Jakarta: Ghalia Indonesia.Gujarati, Damodar. (2004). Basic econometrics (ekonometrika dasar). Alih bahasa Sumarno Zain. Jakarta: Penerbit Erlangga.Harris, R. (1995). Cointegration analysis in econometric modelling. New York: Prentice Hall.Iqbal, Muhaimin. (2006). Asuransi umum syariah dalam praktik. Jakarta: Gema Insani.Kurniawan, Todi. (2008). Volatilitas saham syariah (analisis atas Jakarta Islamic Index). Special Edition. Jakarta: Karim Review.Margono. (2004). Metodologi Penelitian Pendidikan. Jakarta: Rineka Cipta.Muhammad Abdulkadir. (2011). Hukum asuransi Indonesia. Edisi 5. Bandung: PT. Citra Aditya Bakti.Mofida, Aini Mufatul. (2011). Metode phillips-perron testuntuk menguji stasioneritas data inflasi. Malang.Nugroho, R.Y. (2009). Analisis faktor penentu pembiayaan perbankan syariah di indonesia: aplikasi model vector error. Tesis tidak diterbitkan. Bogor: Sekolah Pascasarjana, Institut Pertanian Bogor.Otoritas Jasa Keuangan. (2015). Peraturan No 15 / PJOK.04 / 2015 Otoritas Jasa Keuangan, tentang Penerapan Prinsip Syariah di Pasar Modal. Republik Indonesia, Undang-Undang Republik Indonesia Nomor 40 tahun 2014 pasal 1 ayat 30. Tentang Perasuransian.Republik Indonesia. (1995). Undang-Undang Republik Indonesia Nomor 8 tahun 1995 tentang pasar modal (pasar modal)Republik Indonesia. Undang-undang Republik Indonesia pasal 1 (butir 4) UU No. 10 tahun 1998 tentang Perubahan atas UU No. 7 Tahun 1992, tentang PerbankanRusydiana, Aam Slamet. (2009). Mekanisme transmisi syariah pada sistem moneter ganda di indonesia. Bank Indonesia: Buletin Ekonomi Moneter dan Perbankan, 11(4), 345-367.Soemitra, Andri. (2013). Shariah ethical investment products in Indonesian capital market: the debates on their integration process in the transitional stage. Proceeding of Sharia Economics Conference- Hannover. Sugiyono. (2001). Statistika untuk penelitian. Bandung: Alfabeta.